2007
DOI: 10.21773/boun.21.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Direct Selling Ethics: An Exploratory Investigation on Turkish Direct Sellers

Abstract: This study investigates the ethical evaluations of Turkish direct sellers of ethical dilemmas involving consumer complaints. In addition, the effects of market competition as well as some individual factors such as demographics, ethical ideology, locus of control, and Machiavellianism on direct sellers' judgments are also examined. The results suggest that the level of perceived market competition, formal education, external locus of control, relativism, and Machiavellianism explain the ethical evaluations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…According to [6], the view of the overall sales sector scale in direct selling is a valid and reliable indicator of the ideas of sales as profession of students. Direct selling plays an important role in the development of entrepreneurial skills [7]. To acquire knowledge related to the business of direct selling, it was concluded that one should know the marketing plan, its products and the history of the company [8].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…According to [6], the view of the overall sales sector scale in direct selling is a valid and reliable indicator of the ideas of sales as profession of students. Direct selling plays an important role in the development of entrepreneurial skills [7]. To acquire knowledge related to the business of direct selling, it was concluded that one should know the marketing plan, its products and the history of the company [8].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…According to Kavak and Alkibay (2007), studies evaluating salespeople who have face-to-face communications with the buyer are numerous. However, few evaluational studies from the perspective of sales ethics are available.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Lime, cement and bitumen are commonly used additives in soil stabilization. Water content and load-bearing values are optimumised and plasticity is decreased with the addition of lime to natural soil [2]. Fly ash is another substantial additive for soil stabilization.…”
Section: Introductionmentioning
confidence: 99%